Respostas
respondido por:
0
3x+y=19 (1°)
x+4y=43 (2°)
adição
multiplica 2° por (-3)
cancela a x e soma
3x+y=19
-3x-12y=-110
-11y=-110
11y=110
y=110÷11
y=10
substituir y em
3x+y=19
3x+10=19
3x=19-10
3x=9
x=9÷3
x=3
S={(3,10)}
x+4y=43 (2°)
adição
multiplica 2° por (-3)
cancela a x e soma
3x+y=19
-3x-12y=-110
-11y=-110
11y=110
y=110÷11
y=10
substituir y em
3x+y=19
3x+10=19
3x=19-10
3x=9
x=9÷3
x=3
S={(3,10)}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás